Experimental simulation of meteorite ablation during earth entry using a plasma wind tunnel - Loehle, S; Zander, F; Hermann, T; Eberhart, M; Meindl, A; Oefele, R; Vaubaillon, J; Colas, F; Vernazza, P; Drouard, A; Gattacceca, J (IOP Publishing, 2017)
Three different types of rocks were tested in a high enthalpy air plasma flow. Two terrestrial rocks, basalt and argillite, and an ordinary chondrite, with a 10 mm diameter cylindrical shape were tested in order to observe decomposition, potential fragmentation, and spectral signature. The goal was to simulate meteoroid ablation to interpret meteor observation and compare these observations with ground based measurements. The test flow with a local mass-specific enthalpy of 70 MJ kg−1 results in a surface heat flux at the meteorite fragment surface of approximately 16 MW m−2. The stagnation pressure is 24 hPa, which corresponds to a flight condition in the upper atmosphere around 80 km assuming an entry velocity of 10 km s−1. Five different diagnostic methods were applied simultaneously to characterize the meteorite fragmentation and destruction in the ground test: short exposure photography, regular video, high-speed imaging with 10 kHz frame rate, thermography, and Echelle emission spectroscopy. This is the first time that comprehensive testing of various meteorite fragments under the same flow condition was conducted. The data sets indeed show typical meteorite ablation behavior. The cylindrically shaped fragments melt and evaporate within about 4 s. The spectral data allow the identification of the material from the spectra which is of particular importance for future spectroscopic meteor observations. For the tested ordinary chondrite sample a comparison to an observed meteor spectra shows good agreement. The present data show that this testing methodology reproduces the ablation phenomena of meteoritic material alongside the corresponding spectral signatures.